Research of Audit Services Market in Bulgaria - Petrova, Daniela; Atanasova, Adriana (Research Papers, 2024)
The degree of concentration in the audit services market is a worrying factor for both researchers and regulators, who should determine the policies and potential regulatory impacts affecting concentration. The discussions have been provoked by the increasing level of concentration (despite different levels in individual countries) over the last decade. The lack of similar research in Bulgaria is an obstacle to the market entry of new audit firms and at the same time makes it difficult to regulate this market and this provokes research interest. The results of the research confirm the thesis that the levels of concentration in the audit services market in Bulgaria are significantly lower than those in other European countries, as well as the average value for EU countries.